2012
DOI: 10.1039/c2nr30688c
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ohmic nanocontacts via surface modification for nanowire-based electronic and optoelectronic devices: ZnO nanowires as an example

Abstract: We demonstrated a nanocontacting scheme using a focus ion beam (FIB) system without further heat treatment for ZnO nanowires. This scheme includes Ga ion surface modification and direct-write Pt deposition induced by Ga ion, leading to an Ohmic nanocontact with a specific contact resistance as low as 2.5 × 10(-6)Ω cm(2). Temperature-dependent measurements show that the transport of the FIB-Pt contact on the ZnO nanowire with local surface modification is governed by field emission tunneling. Taking advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…By this model fitting we extract a contact resistivity of 2.59 ± 0.08 mΩ‐cm 2 for a 140 nm wire based on a contact area of 1.78 × 10 −9 cm 2 . Although these contacts have higher resistivity than contacts prepared by 30 kV Ga beam pre‐treatment, the contacts were prepared without implanting the wire with an n‐type dopant or depositing multiple metal layers such as Ti/Au contacts.…”
Section: Resultsmentioning
confidence: 99%
“…By this model fitting we extract a contact resistivity of 2.59 ± 0.08 mΩ‐cm 2 for a 140 nm wire based on a contact area of 1.78 × 10 −9 cm 2 . Although these contacts have higher resistivity than contacts prepared by 30 kV Ga beam pre‐treatment, the contacts were prepared without implanting the wire with an n‐type dopant or depositing multiple metal layers such as Ti/Au contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Direct-written Pt deposition by FIB was used to prepare Pt electrodes. Even though the work function of Pt (~6.1 eV) is higher than that of pure ZnO (~5.1 eV), the contact electrodes of ZnO/Pt fabricated by Ga ion surface modification process and direct-written Pt deposition could still be Ohmic [ 28 ]. Figure 2 c shows the I – V characteristics of the ZnO NW and Sb–ZnO NW.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical properties of nanowire-based FET devices sensitively depend on their size and shape, defects and impurities, and surface states or defects [7][8][9]. Moreover, it has been generally accepted that the contacts between the nanowire and the metal electrodes play also an important role in the charge transport properties of nanowire-based FETs due to their large surface-to-volume ratio coupled with unique geometry [10][11][12]. For example, Lee and coworkers reported the distinct electrical transport features of FETs made from ZnO nanowires with two different types of geometric properties: one type consisted of corrugated nanowires with a relatively smaller diameter and higher density of surface states or defects, and the other type involved smooth ZnO nanowires with a relatively larger diameter and lower density of surface states or defects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lord et al [10] showed that the electrical transport behavior of nanocontacts between ZnO nanowires and Au metals can switch from Schottky to Ohmic depending on the size of the metal contact in relation to the nanowire diameter. Jo et al [11] and He et al [12] demonstrated the influence of the contact resistance on the electrical properties in In 2 O 3 and ZnO nanowires, respectively.…”
Section: Introductionmentioning
confidence: 99%